Astrocyte-mediated disruption of ROS homeostasis in Fragile X mouse model. (June 2021) - Vandenberg, Gregory G.; Dawson, Neal J.; Head, Alison; Scott, Graham R.; Scott, Angela L.
Abstract: Astrocytes, glial cells within the brain, work to protect neurons during high levels of activity by maintaining oxidative homeostasis via regulation of energy supply and antioxidant systems. In recent years, mitochondrial dysfunction has been highlighted as an underlying factor of pathology in many neurological disorders. In animal studies of Fragile X Syndrome (FXS), the leading genetic cause of autism, higher levels of reactive oxygen species, lipid peroxidation, and protein oxidation within the brain indicates that mitochondria function is also altered in FXS. Despite their integral contribution to redox homeostasis within the CNS, the role of astrocytes on the occurrence or progression of neurodevelopmental disorders in this way is rarely considered. This study specifically examines changes to astrocyte mitochondrial function and antioxidant expression that may occur in FXS. Using the Fmr1 knockout (KO) mouse model, mitochondrial respiration and reactive oxygen species (ROS) emission were analyzed in primary cortical astrocytes. While mitochondrial respiration was similar between genotypes, ROS emission was significantly elevated in Fmr1 KO astrocytes. Notably, NADPH-oxidase 2 expression in Fmr 1 KO astrocytes was also enhanced but only changes in catalase antioxidant enzyme expression were noted. Characterization of astrocyte factors involved in redox imbalance is invaluable to uncovering potential sources of oxidative stress in neurodevelopmental disorders and more specifically, the intercellular mechanisms that contribute to dysfunction in FXS. Highlights: Astrocyte ROS emission contributes to oxidative imbalance in Fragile X Syndrome. Astrocyte-mediated antioxidant system appears insufficient to compensate for changes in cellular ROS load. Upregulation of NOX2 enzymes in FMRP-deficient astrocytes may help drive loss of redox homeostasis within the CNS.